2010
DOI: 10.1002/aqc.1122
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional dispersal of aquatic invertebrates via footwear and motor vehicles in a Mediterranean wetland area

Abstract: ABSTRACT1. Several human activities, such as actions for nature conservation, research and recreational activities, are closely associated with inland aquatic habitats that are usually considered as isolated island habitats. In this study, the possibility of unintentional dispersal of aquatic invertebrates among water bodies via footwear and motor vehicles was investigated.2. Mud samples collected from boots and from the tyres and wheel cases of cars used for field work by biologists (Camargue, Southern France… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 42 publications
4
75
1
1
Order By: Relevance
“…In the present survey, we found higher richness of invertebrate taxa hatching from boots mud (including copepod and notostracan species) than in similar studies (Waterkeyn et al 2010a), although this variation depends on the taxonomical resolution attained in the survey. These authors also found ostracods and cladocerans with high prevalence in waterproof boots.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…In the present survey, we found higher richness of invertebrate taxa hatching from boots mud (including copepod and notostracan species) than in similar studies (Waterkeyn et al 2010a), although this variation depends on the taxonomical resolution attained in the survey. These authors also found ostracods and cladocerans with high prevalence in waterproof boots.…”
Section: Discussioncontrasting
confidence: 51%
“…Anostraca, Ostracoda, and Cladocera were the groups that hatched in higher proportions of individuals, but the Protozoa (88 %) and Ostracoda (40 %) were the most prevalent in the analyzed samples. Waterkeyn et al (2010a) found all of these groups to be present in the egg bank of water bodies in the study area, and demonstrated that invertebrate propagules were transported by the sediment attached to footwear. This nonstandard vector may be an important mechanism connecting biogeographic islands and affecting metacommunity dynamics.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…What Old Romans called ''Mare Nostrum'' was crossed by several trade routes and people living on its shores have been sailing across it since at least 5,000 years, founding settlements and actively transporting goods (and drinking water) all around the lands surrounding this sea (Abulafia, 2011). Further to historical reasons, other more recent human activities still contribute to freshwater organisms dispersal: construction of canals connecting separated watersheds (Dumont, 1995), recreational boating (Albrecht et al, 2009;Bruckerhoff et al, 2014), trade in ornamental species for aquaria (Padilla & Williams, 2004;Marrone & Naselli-Flores, 2011;Havel et al, 2014), and ecotourism and/or scientific field-work (Waterkeyn et al, 2010) have been found to be responsible of dispersal and new species (even invasive) introductions. Trading of living fish for sport and professional fishing can be also responsible for the accidental introductions of (micro)organisms and a huge number of nonindigenous species are reported as ''invaders'' in freshwater ecosystems at a high frequency (Ruiz & Carlton, 2003;Havens & Beaver, 2014).…”
Section: Dispersal By Human Activitiesmentioning
confidence: 99%